Perancangan dan Implementasi Aplikasi Pendukung Keputusan Penentuan Rumah Subsidi Terbaik Menggunakan Metode MOORA - Sinulingga, Silvani; Halawa, Cerah K.; Marpaung, Preddy; Pasaribu, Sutrisno A. (Jurnal Sistem Informasi dan Teknologi Jaringan, 2024)
Designing and implementing a decision support application for determining the best-subsidized housing using the MOORA (Multi-Objective Optimization based on Ratio Analysis) method is an important step in helping the community, especially low-income communities (MBR). One of the areas where there are subsidized houses is Tanjung Morawa District, Deli Serdang. Where there is no web-based application system or similar that can distribute information about subsidized housing to the community in that area. Therefore, it is necessary to build a decision-support application using a method. The MOORA method is very suitable for use in this context because of its ability to handle decision-making problems that involve many criteria. The application designed and built using the MOORA method is able to produce the best housing recommendations based on the highest ranking and calculation results for each predetermined criteria, where the highest result is ranking 1, namely Grya Seruni housing.